ACCOUNTABILITY IN THE PUBLIC SECTOR: A REFLECTION BEYOND REPORTING (REMUNOM, 2024)
This article analyzes contemporary conceptions of public accountability, aiming to synthesize the literature on the subject and highlight the variety of perspectives and approaches, both in international and Brazilian contexts. In addition to traditional notions of accountability, such as responsibility and transparency, the study emphasizes its importance as one of the pillars of modern governance, essential for strengthening democracy. Public accountability enables citizens to demand the fulfillment of electoral promises made by elected leaders and hold them accountable for their actions, emphasizing the importance of public involvement in this process. The literature review was based on sources from contemporary literature to support the study. The analysis of the literature indicates that public accountability goes beyond responsibility and transparency, incorporating concepts such as transparency, publicity, participation, citizen engagement, and other elements essential for effective democratic governance.